The Hygiene Hypothesis And Covid-19: A Look At The Evidence And New Perspectives - Peppy Nawangsasi; Ronald Pratama Adiwinoto; Verna Biutifasari; Tamam Jauhar; Wahyu Prasasti Mutiadesi (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
The hygiene hypothesis postulates that early-life exposure to infectious agents and microbes has a significant impact on the maturation of the immune system, providing protection against allergies and autoimmune diseases.Recent studies have challenged the hypothesis's universality, suggesting that it might only be relevant in developed countries. New perspectives on the hygiene hypothesis propose a multifaceted theory that considers not only microbial exposure but also factors such as diet, stress, and the environment. The role of specific immune cells in the development of allergies and autoimmune diseases has been emphasized, and innovative therapies based on manipulation of immune cells have been proposed. The importance of reconciling the hygiene hypothesis with recent insights into the human microbiome and the importance of maintaining a balance between hygiene and microbial exposure is also emphasized. Lastly, the article delves into the hygiene hypothesis, investigates the connection between gut microbiota dysbiosis and the development of allergies and autoimmune diseases, and examines the influence of COVID-19 on both gut microbiota and immune function.Keywords: allergies and autoimmune diseases, gut microbiome dysbiosis